Causes of Post Surgery Disputes between Plastic Reconstructive and Aesthetic Surgeons with Patients - Endang Sri Sarastri; Liliana Tedjosaputro; M.C. Inge Hartini (Institute of Medico-legal Publications Pvt Ltd, 2022)
Advances in science and technology and the ability, skills, and soul of the art of Plastic Reconstructiveand Aesthetic Surgeons can change human organs according to the patient’s wishes to improve one’sappearance to become more beautiful or handsome. Aesthetic plastic surgery is not performed totreat physical disabilities, in contrast to reconstructive plastic surgery, which aims to treat physicaldisabilities. However, misunderstandings or failures can occur because Plastic Reconstructive andAesthetic Surgeons are also human, so it does not give satisfaction to the results expected by the patient.Not infrequently, the misunderstanding peaked, resulting in a dispute between the doctor of PlasticReconstructive and Aesthetic Surgeons with the patient. This research method is normative juridicalresearch empirical. The research specification in this study is descriptive-analytical. Research conductedusing secondary data sources that include primary legal materials in norms, basic rules, laws, andregulations. The results of this study explain that Plastic Reconstructive and Aesthetic Surgeons shouldnot give an appointment or guarantee success on the surgical efforts that have been done because thereare other factors beyond their power as a doctor. The doctor should explain the risks and complicationsthat may occur. In addition, before surgery, it is recommended that a complete agreement be madewith the patient, and the patient understands and understands the risks or possibilities that can occurpostoperatively in the future. The doctor and patient agreement are made in full and detailed in writtenform before medical action is carried out by involving a notary public to ensure legal certainty, fairness,and benefit.